2020
DOI: 10.21203/rs.2.15436/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Macular hole edge morphology predicts restoration of postoperative retinal microstructure and functional outcome

Abstract: Background: To investigate the association between iOCT feature in macular hole (MH) surgery and the restoration of the retina microstructure and visual outcomes. Methods: This was a case series study including fifty-three eyes of 53 patients with macular hole were recruited. According to the morphological characteristics of the hole edge as imaged by iOCT after ILM peeling, all patients were divided into three groups: fovel flap group, hole-door group, and negative group. The restoration of the retina microst… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Minimum diameter of MH (equivalent to MH size) is one of the most studied parameters. Other parameters include hole height and inner segment/outer segment junction defect length as well as ratios such as the macular hole index (MHI) [26]. In our study, we identified the presence of elevated edges on preoperative OCT as a predictive factor of final VA ≥70 ETDRS letters.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Minimum diameter of MH (equivalent to MH size) is one of the most studied parameters. Other parameters include hole height and inner segment/outer segment junction defect length as well as ratios such as the macular hole index (MHI) [26]. In our study, we identified the presence of elevated edges on preoperative OCT as a predictive factor of final VA ≥70 ETDRS letters.…”
Section: Discussionmentioning
confidence: 75%
“…In our study, we identified the presence of elevated edges on preoperative OCT as a predictive factor of final VA ≥70 ETDRS letters. A recent study by Tao et al investigated the impact of postoperative hole edge configurations on visual outcomes and found that MH morphologies with extra flaps of tissue (n � 14) had significantly better final VA and postoperative restoration of ELM than MH without any specific configuration (n � 24) (p � 0.012) [26]. However, to our knowledge, no studies have looked at elevated MH edge as a preoperative factor.…”
Section: Discussionmentioning
confidence: 98%
“…Eyes with the hole-doorsign had a 100% rate of closure without an neurosensory defect compared to 60% of the eyes without the hole-door-sign [61]. The studies of Inoue et al and Tao et al confirmed the predictive value of the hole-door-sign for macula hole closure, however, the authors reported contradicting results regarding the postoperative visual acuity in eyes with the hole-door-sign [62,63].…”
Section: Retinal Membrane Peeling and Macular Hole Surgerymentioning
confidence: 99%